Thermocatalytic CO2 Conversion over a Nickel-Loaded Ceria Nanostructured Catalyst: A NAP-XPS Study - Barroso Bogeat, Adrián (2021)
Despite the increasing economic incentives and environmental advantages associated to their substitution, carbon-rich fossil fuels are expected to remain as the dominant worldwide source of energy through at least the next two decades and perhaps later. Therefore, both the control and reduction of CO2 emissions have become environmental issues of major concern and big challenges for the international scientific community. Among the proposed strategies to achieve these goals, conversion of CO2 by its reduction into high added value products, such as methane or syngas, has been widely agreed to be the most attractive from the environmental and economic points of view. In the present work, thermocatalytic reduction of CO2 with H2 was studied over a nanostructured ceria-supported nickel catalyst. Ceria nanocubes were employed as support, while the nickel phase was supported by means a surfactant-free controlled chemical precipitation method. The resulting nanocatalyst was characterized in terms of its physicochemical properties, with special attention paid to both surface basicity and reducibility. The nanocatalyst was studied during CO2 reduction by means of Near Ambient Pressure X-ray Photoelectron Spectroscopy (NAP-XPS). Two different catalytic behaviors were observed depending on the reaction temperature. At low temperature, with both Ce and Ni in an oxidized state, CH4 formation was observed, whereas at high temperature above 500 °C, the reverse water gas shift reaction became dominant, with CO and H2O being the main products. NAP-XPS was revealed as a powerful tool to study the behavior of this nanostructured catalyst under reaction conditions.